2013
DOI: 10.5539/ijbm.v8n14p89
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Intention to Leave Towards Employee Engagement among Young Bankers in Malaysia

Abstract: The purpose of the study is to investigate the influence of intention to leave towards employee engagement among young employees, in the perspective of Malaysian commercial banks. The study distributed 450 questionnaires to young bankers who are employed with commercial banks in Malaysia through "Drop off" and "Pick up" method. The method was employed due to the confidentiality practiced by the banks. This method of survey distribution was proven effective whereby 412 responses were gathered which demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…The non-managerial bank employees in Malaysia have been known to frequently change their jobs and this has resulted in high turn overs in the local banking industry (Hussain, Yunus, Ishak & Daud 2013). Ghosh, Rai and Sinha (2014) in their study among bank employees found that the turnover rate is relatively high in the banking sector and this has been contributed to lack of affective commitment among the employees.…”
Section: Introductionmentioning
confidence: 99%
“…The non-managerial bank employees in Malaysia have been known to frequently change their jobs and this has resulted in high turn overs in the local banking industry (Hussain, Yunus, Ishak & Daud 2013). Ghosh, Rai and Sinha (2014) in their study among bank employees found that the turnover rate is relatively high in the banking sector and this has been contributed to lack of affective commitment among the employees.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Section 5 discussed employee’s performance consisting of 19 indicators. For latent constructs, job engagement and organization engagement, the indicators are adopted and revised from Juhdi, Pa’wan, and Milah (2012), Saks (2006), Hussain, Yunus, Ishak, and Daud (2013). Meanwhile, HR practices measure on recruitment, training and development and compensation and rewards.…”
Section: Methodsmentioning
confidence: 99%
“…Section IV includes individual work performance which consists of nineteen indicators. The indicators for employee engagement are adopted and a revise from originally proposed by Juhdi et al (2012), Saks (2006) and Hussain et al (2013). Meanwhile, human resource practices measure the recruitment, training and development and compensation and rewards.…”
Section: Methodsmentioning
confidence: 99%